Demethylmenaquinone Methyl Transferase Is a Membrane Domain-Associated Protein Essential for Menaquinone Homeostasis in Mycobacterium smegmatis - Puffal, Julia; Mayfield, Jacob A.; Moody, D. Branch; Morita, Yasu S. (Frontiers in Microbiology, 2018)
The intracellular membrane domain (IMD) in mycobacteria is a spatially distinct region of the plasma membrane with diverse functions. Previous comparative proteomic analysis of the IMD suggested that menaquinone biosynthetic enzymes are associated with this domain. In the present study, we determined the subcellular site of these enzymes using sucrose density gradient fractionation. We found that the last two enzymes, the methyltransferase MenG, and the reductase MenJ, are associated with the IMD in Mycobacterium smegmatis. MenA, the prenyltransferase that mediates the first membrane-associated step of the menaquinone biosynthesis, is associated with the conventional plasma membrane. For MenG, we additionally showed the polar enrichment of the fluorescent protein fusion colocalizing with an IMD marker protein in situ. To start dissecting the roles of IMD-associated enzymes, we further tested the physiological significance of MenG. The deletion of menG at the endogenous genomic loci was possible only when an extra copy of the gene was present, indicating that it is an essential gene in M. smegmatis. Using a tetracycline-inducible switch, we achieved gradual and partial depletion of MenG over three consecutive 24 h sub-cultures. This partial MenG depletion resulted in progressive slowing of growth, which corroborated the observation that menG is an essential gene. Upon MenG depletion, there was a significant accumulation of MenG substrate, demethylmenaquinone, even though the cellular level of menaquinone, the reaction product, was unaffected. Furthermore, the growth retardation was coincided with a lower oxygen consumption rate and ATP accumulation. These results imply a previously unappreciated role of MenG in regulating menaquinone homeostasis within the complex spatial organization of mycobacterial plasma membrane.